Using drama to teach personal, social and emotional skills - O'Hanlon, Jacqui
Originally developed for deaf children, this innovative and successful drama programme addressing personal, social and emotional needs can benefit all children in primary schools. The interactive and lively ideas cover a variety of themes from empathy to assertiveness